Genetic screening of tuberous sclerosis complex in Sicily with a focus on neurological manifestations - Andrea Domenico Praticò; Claudia Di Napoli; Stefania Salafia; Edoardo Dammino; Maria Piccione; Francesco Calì; Renato Scifo; Michele Vecchio; Andrea Zonta; Maria Bonsignore; Maurizio Elia; Manuela Lo Bianco; et al. (Scientific Reports)
Abstract Tuberous Sclerosis Complex (TSC) is an autosomal dominant disorder characterized by widespread hamartomas and prominent neurological involvement. It results from pathogenic variants in the TSC1 or TSC2 genes, leading to hyperactivation of the mTOR pathway and consequent dysregulation of cell growth. These tumor suppressor genes encode hamartin and tuberin, proteins critical for regulating cell proliferation, neuronal excitability and synaptogenesis. In this retrospective study, we analyzed clinical, genetic and radiological features of 81 TSC patients from Sicily, focusing on genotype-phenotype correlations and intergroup comparisons. Pathogenic TSC2 variants were more common than pathogenic TSC1 variants (61.7% vs. 38.3%). Patients with pathogenic TSC2 variants tended to exhibit a higher frequency of weekly seizures, a higher prevalence of infantile spasms and hypsarrhythmia compared to those with pathogenic TSC1 variants, consistent with a more severe phenotype. Interestingly, TSC1 patients exhibited a higher incidence of radial bands, while TSC2 patients harbored a larger average size of tubers and subependymal nodules. Cognitive and behavioral disorders were similarly distributed, although TSC1 patients had higher rates of normal or borderline cognitive function, while TSC2 patients had more severe neuropsychiatric profiles compared to TSC1. To our knowledge, this is the first comprehensive TSC1 and TSC2 mutational analysis and genotype-phenotype correlation study carried out in a large cohort of Sicilian patients affected by TSC. Our findings contribute to regional and global data on TSC, emphasizing the utility of genotype-informed management strategies.